1969
DOI: 10.1139/v69-117
|View full text |Cite
|
Sign up to set email alerts
|

Metal ion initiated halogenation reactions of N-haloamines

Abstract: The metal ion catalyzed chlorination of hydrocarbon substrates by N-chloroamines and imides in acid media proceeds by a free radical chain mechanism. Reactions of four different N-chloro halogenating reagents with cuprous chloride, ferrous sulfate, and ferrous chloride initiators have been investigated. Contrary to the previously reported observations no experimental differences were observed in the halogenation reactions of individual N-halo compounds or with the different initiators. The chain carrying speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

1970
1970
2011
2011

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…Nevertheless, one analogy with the present data is the fact that the major product of this, and related, free radical halogenations (5,6), is the isomer substituted at the penultimate position. Reactions of lactones with 38% hydrochloric acid In marked contrast to the facile conversion of n-alkano-yor 6-lactones into haloacids by HI or HBr, little reaction occurred under reflux in HCl (37%).…”
Section: Sources Of Variations In Haloacid Compositionsupporting
confidence: 81%
“…Nevertheless, one analogy with the present data is the fact that the major product of this, and related, free radical halogenations (5,6), is the isomer substituted at the penultimate position. Reactions of lactones with 38% hydrochloric acid In marked contrast to the facile conversion of n-alkano-yor 6-lactones into haloacids by HI or HBr, little reaction occurred under reflux in HCl (37%).…”
Section: Sources Of Variations In Haloacid Compositionsupporting
confidence: 81%
“…A reinvestigation suggested that halogenation proceeded via the chlorine atom as the chain-propagating species (eq 113). 243 The hypothesis was based on the fact that the isomer…”
Section: Arsenic and Antimony Compoundsmentioning
confidence: 99%
“…The substructure of the modern reef is Miocene in age and probably much of the reef volume is Miocene (Tanner 1969). During the early Miocene, much of the Papuan Basin appears to have been divided into basins and shelf areas by a system of more or less continuous barrier or elongate reef zones.…”
mentioning
confidence: 99%